1980
DOI: 10.1148/radiology.137.3.6777827
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling of hypoxic-tumor therapy using neutron brachytherapy.

Abstract: Fast-neutron-beam therapy and low-dose-rate fast-neutron intracavitary therapy of cervical carcinoma are effective in producing regression of advanced tumors. However, effectiveness is critically dependent on the schedule by which they are used in combination with fractionated external low-linear-energy-transfer (LET) therapy. Neutron-beam therapy is now alternated frequently with fractionated external radiotherapy (mixed beam). Intracavitary neutron therapy, scheduled before fractionated external-beam photon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The clearance of tumor was more rapid by the early application of neutron therapy than by a delayed application, when combined with fractionated radio therapy [16,17], The results of this study indicate that effective therapy must be optimally sequenced in the treatment course and combined with modalities that increase the likelihood of tumor control. Impor tant physiological contributions of vascular factors to radiation response [11,[25][26][27] and reoxygenation was suggested by the failure of local control observed in 2 patients with severe small vessel vascular disease.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The clearance of tumor was more rapid by the early application of neutron therapy than by a delayed application, when combined with fractionated radio therapy [16,17], The results of this study indicate that effective therapy must be optimally sequenced in the treatment course and combined with modalities that increase the likelihood of tumor control. Impor tant physiological contributions of vascular factors to radiation response [11,[25][26][27] and reoxygenation was suggested by the failure of local control observed in 2 patients with severe small vessel vascular disease.…”
Section: Discussionmentioning
confidence: 76%
“…They are in accord with reports of (1) lesser radioresponsiveness of anemic patients [25]; (2) improvement in local control and survival by blood transfusions to anemic cervix tumor-bearing patients [2,25], and (3) improved control of tumors by oxygen breathing during radio therapy [13] or by high-pressure oxygen tanks used at the time of treatment [33]. In addition, this paper pro vides evidence for the importance of the time and scheduling of hypoxic tumor therapy and the great importance of reoxygenation [17]. The quantity of hypoxic tumor destroyed was probably further enhanced by the reoxygenation of hypoxic tumor because of the more effective early therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While such investigations will be undertaken in studies underway, it is well to note that the prognosis of the cancers treated with Cf-252 was so grave and inevitably fatal that clinical trials were needed if treatment was to be improved [16,19]. Concurrent basic biological studies also need to be carried out since observed tumor responses to neutrons were so different [14,15] that the simple adjustment of a prescribed dose by a RBE value may not only mislead but actually misguide the intent of the planned therapeutic program. The present data also revealed a low RBE without a significant change in survival curve shape.…”
Section: Discussionmentioning
confidence: 99%
“…Implant radiotherapy was of several hours (4-8 h) duration and used Cf-252, a radioactive isotope of the transplutonium series which emits fast neutrons of 2.3 MeV average energy (8). NT has been carried out using specially designed hollow plastic afterloading applicators positioned in the tumor using CT scanning and orthogonal x-rays (9).…”
Section: Brain Implant and Radiotherapymentioning
confidence: 99%